2019
DOI: 10.1001/jamaoncol.2019.0250
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib Plus Hepatic Arterial Infusion of Oxaliplatin, Fluorouracil, and Leucovorin vs Sorafenib Alone for Hepatocellular Carcinoma With Portal Vein Invasion

Abstract: IMPORTANCE Sorafenib is the first-line treatment for hepatocellular carcinoma with portal vein invasion; however, it has shown unsatisfactory survival benefit. Sorafenib plus hepatic arterial infusion chemotherapy (HAIC) of oxaliplatin, fluorouracil, and leucovorin (FOLFOX) has shown promising results for these patients in a previous phase 2 study.OBJECTIVE To investigate the efficacy and safety of sorafenib plus HAIC compared with sorafenib for hepatocellular carcinoma with portal vein invasion. DESIGN, SETTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
407
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 392 publications
(458 citation statements)
references
References 40 publications
(75 reference statements)
10
407
4
1
Order By: Relevance
“…Asian dug approvals and reimbursements for HCC according to country, and ESMO-Magnitude of Clinical Benefit Score (MCBS) 125 Drugs been supported by a Chinese study showing the superiority of hepatic arterial infusion of FOLFOX plus sorafenib versus sorafenib alone in patients with advanced HCC. 98 Thus, HAIC either alone or in combination with sorafenib may be an option for certain selected patients with advanced HCC. Finally, several randomised phase III clinical trials have been conducted to investigate the potential of other targeted agents in the first-line treatment of HCC compared with sorafenib.…”
Section: Resultsmentioning
confidence: 99%
“…Asian dug approvals and reimbursements for HCC according to country, and ESMO-Magnitude of Clinical Benefit Score (MCBS) 125 Drugs been supported by a Chinese study showing the superiority of hepatic arterial infusion of FOLFOX plus sorafenib versus sorafenib alone in patients with advanced HCC. 98 Thus, HAIC either alone or in combination with sorafenib may be an option for certain selected patients with advanced HCC. Finally, several randomised phase III clinical trials have been conducted to investigate the potential of other targeted agents in the first-line treatment of HCC compared with sorafenib.…”
Section: Resultsmentioning
confidence: 99%
“…• Select patients likely to benefit, including those refractory to systemic therapy with advanced vascular invasion 31,[43][44][45] Alternative therapy: systemic therapy ALBI, albumin-bilirubin; EASL, European Association for the Study of the Liver; HAIC, hepatic arterial infusion chemotherapy; HCC, hepatocellular carcinoma; ILCA, International Liver Cancer Association; PS, performance status; RFA, radiofrequency ablation; TACE, transarterial chemoembolization.…”
Section: General Mattersmentioning
confidence: 99%
“…The mOS of the patients treated with HAIC and sorafenib was 315 days, which was significantly longer than that treated with HAIC alone (197days) [30]. A prospective randomized controlled trial recruited 247 HCC patients with PVTT showed that HAIC combined with sorafenib could significantly prolong the survival time (mOS: 13.37 vs. 7.13 months, respectively), and the progression-free survival time (median: 7.03 vs 2.6 months, respectively) of patients compared with sorafenib alone [31]. The mOS of patients in combination therapy group and sorafenib monotherapy group was 18.17 and 10.87 months, respectively in type I -II PVTT subgroup, 13.47 and 6.27 months respectively in type III PVTT subgroup, 9.47 and 5.5 months respectively in type IV PVTT subgroup [31].…”
Section: Haic Combined With Sorafenibmentioning
confidence: 99%